Pengungkapan Risiko dan Peluang sebagai Informasi Forward-Looking dalam Integrated Reporting - Dyah Hanila Yuniawanty; Ika Permatasari (CV. Kalimasada Group, 2026)
Integrated reporting has developed as a reporting approach that integrates financial and non-financial information to provide a more comprehensive picture of a company's strategy, governance, performance, and prospects in the value creation process. Within this framework, the disclosure of risks and opportunities becomes an important element because it provides relevant information for investors in assessing the company's performance, prospects, and sustainability. This study conceptualizes the quality of risk and opportunity disclosure in integrated reporting through a comparison of reporting practices in companies in South Africa and Indonesia. The review shows that companies in South Africa tend to present disclosures that are more integrated with strategy and long-term value creation, whereas companies in Indonesia still emphasize disclosures of risks that are descriptive and mitigative. The difference indicates the importance of disclosure quality in supporting decision-making.